Scrub typhus among patients with acute febrile illness in Bhutan: A cross‐sectional study - Karma Norbu; Karma Dema; Kuenga Choden; Tshewang Gyeltshen (Public Health Challenges, 2023)
Abstract Introduction Early diagnosis and treatment plays an important role in preventing mortality in scrub typhus infection. In districts situated in the subtropical region of Bhutan, scrub typhus remains an important aetiology among those with acute febrile illness. Zhemgang is one district at 572 m above sea level with warm humid climate, and the majority of population are involved in farming and livestock rearing. Methods This was a cross‐sectional study among patients with acute febrile illness in Zhemgang district, Bhutan, tested for scrub typhus rapid diagnostic kits. Variables were extracted from the laboratory registers for tests conducted between January 2019 and December 2020. Risk factors associated with scrub typhus were assessed using logistic regression. This study was approved by the Research Ethics Board of Health, Bhutan. Results There were 922 tests conducted for scrub typhus. The test positivity rate was 8.2% (n = 76) with the highest reported in Panbang Hospital (43, 56.6%) followed by Yebilaptsa Hospital (27, 35.5%) and Zhemgang Hospital (6, 7.9%). A higher number of cases were detected in females (44, 57.9%) and in the month of September (17, 16.3%). The factors associated with scrub typhus positivity rates were hospitals located in lower altitudes, age, sex and seasons (spring, summer, autumn and winter). Conclusions One tenth of patients with acute febrile illness tested positive for scrub typhus with the adequate volume of tests prescribed by the clinicians. Our study shows that summer months recorded higher proportions of scrub typhus infection.